Comparison between Tramadol and Butorphanol for Treating Postoperative Catheter-Related Bladder Discomfort: A Randomized Controlled Trial. (28th December 2021) - Lin, Feihong; Shao, Kaiyang; Pan, Wei; Liang, Dongdong; Zhao, Zhangfan; Yuan, Jixiang; Wang, Junlu; Lv, Ya
Abstract : Background . Intraoperative catheterization often leads to postoperative catheter-related bladder discomfort (CRBD) during the restoration period. This study aimed to assess the curative effect of butorphanol as a K receptor agonist in the treatment of postoperative CRBD. Patients and Approaches . Sixty patients with CRBD who underwent elective nonurological surgery at the postanesthesia care unit were randomly and evenly assigned to two groups. The control group was slowly injected with tramadol 1.5 mg/kg using a Murphy dropper, whereas the experimental group was intravenously injected with butorphanol 0.02 mg/kg. Severity, pain score, and sedation score of CRBD were evaluated at 0 min, 5 min, 15 min, 30 min, 1 h, and 6 h later. Results . The severity score of CRBD and visual analog scale pain score were lower in the butorphanol group than in the control group, whereas the sedation score was higher in the butorphanol group than in the control group. Conclusion . Butorphanol relieves on postoperative urination discomfort and pain compared with tramadol.